2021
DOI: 10.1155/2021/5590315
|View full text |Cite
|
Sign up to set email alerts
|

Game Analysis of Dynamic Planning Evolution for the Optimization of Community Governance Structure in Smart Cities

Abstract: In this paper, we study the structural optimization of community governance in smart cities and optimize the structure based on the game analysis of dynamic planning evolution. Theoretically, the connotation and extension of the concept of “self-organization” are cleared, and the environment and conditions of community self-organization formation, the formation process of community self-organization, and the types of community self-organization are discussed. The so-called “self-organization” is a process of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This study found that smart communities make up for the blind ends and shortcomings of traditional communities and provide technical support for CG. Some scholars believe that digital communities play an increasingly important role in preventing and resisting emergencies and achieving sustainable community development (e.g., Liang, 2021;Okada, 2018;Tang, 2022). Tang (2022) believes that smart community platforms play an important role in strengthening the construction of underlying infrastructure, support platforms, and basic databases.…”
Section: Theme 3: Governance Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that smart communities make up for the blind ends and shortcomings of traditional communities and provide technical support for CG. Some scholars believe that digital communities play an increasingly important role in preventing and resisting emergencies and achieving sustainable community development (e.g., Liang, 2021;Okada, 2018;Tang, 2022). Tang (2022) believes that smart community platforms play an important role in strengthening the construction of underlying infrastructure, support platforms, and basic databases.…”
Section: Theme 3: Governance Technologymentioning
confidence: 99%
“…Tang (2022) believes that smart community platforms play an important role in strengthening the construction of underlying infrastructure, support platforms, and basic databases. Liang (2021) studied the structural optimization problem of smart city CG. On this basis, the positive significance of community self-organization to community cultural governance is confirmed.…”
Section: Theme 3: Governance Technologymentioning
confidence: 99%